Micropropagation Of Fig (Ficus Carica) Cv.japanese Btm 6 - Lee, Yong Jun (2024)
Ficus carica L., commonly known as the fig tree and belonging to the Moraceae family, is cultivated in subtropical and Mediterranean regions worldwide. This fruit-bearing tree is rich in natural fibre, minerals, and vitamins. However, conventional propagation methods, such as grafting, hardwood cutting, and air layering, are inefficient for establishing viable plant stocks in Malaysia. The primary factor to this inefficiency is the suboptimal rooting efficiency associated with these conventional propagation techniques. However, experiments have shown that vermicast can enhance root induction, improving the survival rate of plantlets in these methods. Therefore, vermicast can be as an option to help with root induction."Vermicast, a byproduct of organic matter decomposition by earthworms, is known for its advantageous impact on plant growth in agriculture. This study aims to establish methods for the micropropagation of Ficus carica cv. Japanese BTM 6 and to evaluate the regeneration effects of vermicast solution on in vitro shoot cultures. Sterile nodal segment explants were subjected to treatments involving various types and concentrations of organic additives, including potato, banana, and coconut water. The induced shoots were further treated with different combinations and concentrations of cytokinins (meta-topolin, BAP, 2ip, zeatin, and TDZ) and auxins (IAA, IBA, NAA) to promote shoot multiplication. Additionally, the induced shoots were assessed for their response to varying concentrations of vermicast solution (ranging from 5% to 30%) in terms of in vitro shoot and root regeneration. Plantlets with roots were acclimatized with different potting mix and vermicast as the acclimazation media with and without vermicast solution during watering.